2013
DOI: 10.1242/jeb.072751
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish larvae evade predators by sensing water flow

Abstract: SUMMARYThe ability of fish to evade predators is central to the ecology and evolution of a diversity of species. However, it is largely unclear how prey fish detect predators in order to initiate their escape. We tested whether larval zebrafish (Danio rerio) sense the flow created by adult predators of the same species. When placed together in a cylindrical arena, we found that larvae were able to escape 70% of predator strikes (mean escape probability P escape =0.7, N=13). However, when we pharmacologically a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
168
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(179 citation statements)
references
References 68 publications
(103 reference statements)
10
168
1
Order By: Relevance
“…Even at low light levels and overcritical currents, they may respond to hydraulic gradients and drift under certain conditions (Kaminskas 2011;Schludermann et al 2012). Experiments on zebrafish larvae (Danio rerio, Cyprinidae), for instance, showed that rheoreaction is mediated by neuromasts of the lateral line, which enables young fish to sense water flows and orient in currents at night (Olszewski et al 2012;Stewart et al 2013).…”
Section: Active Driftmentioning
confidence: 99%
“…Even at low light levels and overcritical currents, they may respond to hydraulic gradients and drift under certain conditions (Kaminskas 2011;Schludermann et al 2012). Experiments on zebrafish larvae (Danio rerio, Cyprinidae), for instance, showed that rheoreaction is mediated by neuromasts of the lateral line, which enables young fish to sense water flows and orient in currents at night (Olszewski et al 2012;Stewart et al 2013).…”
Section: Active Driftmentioning
confidence: 99%
“…Specifically, fish initiate a C-start when the appearance of the predator, from the perspective of the prey, increases in size above a critical rate (apparent looming threshold) [28], meaning that fish will most probably respond to a close and fast-moving predator. The flow-sensitive lateral line system is also crucial for detecting a predator's attack [64][65][66]. Zebrafish larvae use the lateral line to detect the subtle disturbance of water ahead of a swimming predator [65], and larvae without the lateral line are over three times more likely to be captured [64].…”
Section: (B) Predator Evasionmentioning
confidence: 99%
“…The flow-sensitive lateral line system is also crucial for detecting a predator's attack [64][65][66]. Zebrafish larvae use the lateral line to detect the subtle disturbance of water ahead of a swimming predator [65], and larvae without the lateral line are over three times more likely to be captured [64]. Ecologically divergent populations of three spine stickleback exhibit considerable differences in lateral line morphology [67] that are related to their ecological conditions (e.g.…”
Section: (B) Predator Evasionmentioning
confidence: 99%
“…As aggressive displays typically include body and fin movements that generate hydrodynamic cues (e.g. chases, opercular displays, tail movements, body quivers; Keenleyside and Yamamoto, 1962;McMillan and Smith, 1974;Stewart et al, 2013;Stewart et al, 2014;Yoshizawa et al, 2014), the reception of these signals by the lateral line system is poised to provide crucial information for opponent assessment and to mediate appropriate behavioral decisions.…”
Section: Introductionmentioning
confidence: 99%